Carrying capacity estimation and habitat suitability of Sumatran elephant in Datuk Gedang Wildlife Corridor, Bukit Tigapuluh Landscape, Jambi, Indonesia - NAUFAL FIKRI; DEDE AULIA RAHMAN; NYOTO SANTOSO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fikri N, Rahman DA, Santoso N. 2023. Carrying capacity estimation and habitat suitability of Sumatran elephant in Datuk Gedang Wildlife Corridor, Bukit Tigapuluh Landscape, Jambi, Indonesia. Biodiversitas 24: 5548-5557. Rapid land use changes, including deforestation and land conversion into human areas, lead to the fragmentation of Sumatran elephant (Elephas maximus sumatranus) habitat. This study aimed to assess food capacity and determine habitat suitability for Sumatra elephants in Datuk Gedang Wildlife Corridor Bukit Tigapuluh Landscape. The research was conducted from January to May 2023. Data on potential, productivity, and carrying food capacity were collected with a direct method in the field with vegetation analysis. Carrying capacity estimation is based on data on productivity, land cover area, proper use, and Sumatran elephant food needs in a day. The habitat suitability model used the present coordinate point data from the GPS collar period of January-December 2022 with eight environment variables. The data were then analyzed for the build Sumatera Elephant habitat suitability model using the Maximum Entropy (MaxEnt) algorithm. We recorded 95 species of the potential Sumatran elephant food. The total feed productivity is 1,032,740.722 kg/ha /day and the carrying capacity is 258 elephants. There were three models of habitat suitability categories: high 4,238.66 ha (7%), medium 8,522.34 ha (14%), and low 11,130.36 ha (18%). The studied landscape can adequately accommodate the current population of Sumatran elephants depending on landscape governance (policy and spatial planning) outside conservation areas.